Moderating effects of personal characteristics on intention to be involved in KM process - Mohamed Razi, Mohamed Jalaldeen; Nor Shahriza , Abdul Karim; Norshidah, Mohamed (2013)
This study investigates the contributing factors of intention to be involved in KM process as well as the moderating effects of personal characteristics on intention to be involved in KM process. As the scope of the KM is very wide, this study was confined only to the knowledge creation and sharing processes of KM. Data were collected from 313 executives of seven companies in the Sri Lankan Telecommunication Industry using self-administered questionnaires. There were four significant predictors of intention to be involved in KM process; two KM enablers and two individual acceptance factors; namely ‘trust & collaboration’, ‘ICT use and support for search and sharing’, ‘performance expectancy of KM’, and ‘effort expectancy of KM’. Furthermore, the study found that gender moderates the relationship between ‘ICT use and support for search and sharing’, ‘performance expectancy of KM’ and intention to be involved in KM process. The findings suggest that if the policy makers in the industry are planning to implement KM initiatives, they should consider gender differences of the executive and the strategies should be formulated accordingly.